Dynamic group-based scheduling of machine-to-machine communication for uplink traffic in LTE networks. (2019) - Chen, Yen-Wen; Chu, Yen-Yin; Kung, Chun-Hsien
In wireless machine-to-machine communication, the signalling load and radio resource allocation are critical to successful service because the technology features a large number of connected devices that introduce significant connection- and resource-related signalling overheads to eNodeB. This paper proposes an uplink scheduling scheme to minimise signalling overhead and maximise system throughput in machine-type communication devices (MTCDs) in long-term evolution networks. The proposed scheme dynamically adjusts group members by considering channel conditions and quality of service and applies the allocation-before-request (AbR) concept to allocate the residual bandwidth and realise the above objectives. Exhaustive simulations were conducted to examine the performance of the proposed scheme. The simulation results showed that the proposed scheme achieves not only better system throughput but also decreased buffer status report (BSR) signalling when compared with the static group-based scheme.